2010
DOI: 10.1002/chem.201002252
|View full text |Cite
|
Sign up to set email alerts
|

Graphene‐Based Multifunctional Iron Oxide Nanosheets with Tunable Properties

Abstract: We report the synthesis of graphenes with tunable properties due to the growth of needlelike iron oxide (IO) nanoparticles on their surfaces. The electrical conductivity, flexibility, and magnetic properties of graphene nanosheets (GNSs) could be tuned on demand by fine controlling both the surface coverage and the length of the IO nanoneedles. The degree of coverage of the IO nanoparticles on the surface of the GNSs made it possible to control the resulting properties of the IO/GNSs on demand. As examples of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
35
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(38 citation statements)
references
References 31 publications
(34 reference statements)
0
35
0
Order By: Relevance
“…Several studies on magnetic/graphene composites showed good adsorption in the removal of metal ions from the large volumes of wastewater [20][21][22]. Recently magnetic graphene oxide and magnetic graphene nano composites were using for water treatment and drug delivery [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies on magnetic/graphene composites showed good adsorption in the removal of metal ions from the large volumes of wastewater [20][21][22]. Recently magnetic graphene oxide and magnetic graphene nano composites were using for water treatment and drug delivery [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…They can be easily separated from matrices by an external magnetic field, which makes solid-liquid phase separation fast, simple, as well as highly effective. Therefore, magnetic nanoparticles (MNPs), especially Fe 3 O 4 , have attracted quite a lot of attentions because of the outstanding properties such as easy separation and low toxicity [14][15][16][17]. Das et al [18] have studied the sorption of uranium (VI) on magnetite (Fe 3 O 4 ) nanoparticles, but the sorption capacity is relatively low.…”
Section: Introductionmentioning
confidence: 99%
“…GO or rGO have high surface area, mechanical stability, and surface functional groups, which provide as a good support for other adsorbents [38]. In recent years 2D functionalized graphene nanosheets [39], iron oxide-graphene [40][41], ferric hydroxide-GO [42], magnetic Fe 3 O 4 -GO [43], magnetic Fe 3 O 4 -rGO [44], layered double hydroxides (LDH)-GO [45], magnetic Fe 3 O 4 -LDH-graphene [46], and Fe 3 O 4 -MnO 2 -rGO [47] nanocomposites have been attempted to use as adsorbents for removal of arsenic from water. Oh's group developed a one-pot microwave method to produce 3D graphene-carbon nanotubeiron oxide nanostructures for removal of arsenic from contaminated water [48].…”
mentioning
confidence: 99%